Bird fauna encountered at the main campus of the Islamic University of Gaza, Gaza City, Palestine - ABDEL FATTAH N. ABD RABOU (Society for Indonesian Biodiversity, 2019)
Abstract. Abd Rabou AN. 2019. Bird fauna encountered at the main campus of the Islamic University of Gaza, Gaza City, Palestine. Biodiversitas 20: 604-614. Birds are the most prominent and widespread wildlife species of both natural and urban environments worldwide. The strategic geographic position of Palestine at the meeting point of the three continents; Asia, Africa and Europe, is very crucial for the country's bird diversity. The Gaza Strip has never been studied for bird fauna in its urban environments. Thus, the current study comes to survey the bird fauna at the main campus (82,000 m2) of the Islamic University of Gaza (MC-IUG) as an urban environment. Birds were monitored using direct observations and binoculars for the lasted five years. Bird guidebooks and professional cameras were used throughout the succeeding stages of the study. A total number of 56 bird species, belonging to 26 families and 11 orders were encountered throughout the study at MC-IUG. Passeriformes was the largest order and comprised 35 (62.5%) of the recorded bird species, while the non-passerines constitute the remaining 21 species (37.5%). Muscicapidae was the largest among the recorded families, which was represented by 9 species (16.1%), followed by 8 species of Fringillidae (14.3%) and 5 species of Laniidae (8.9%). Finally, the greening strategy of the Gaza Strip should be adopted by Gazans and the local authorities due to the crucial role of vegetation cover in attracting more biodiversity components; especially bird fauna.